Puerto de Tumaco - Ramírez Moreno, María Camila (Universidad Antonio Nariño, 2023)
Based on reliable reference statisticians, the importance that It has the second most important port in the Colombian Pacific. Information was collected from pages such as the Ministry of Industry, tourism Commerce, Ministry of Transportation, Chamber of Commerce of Tumaco, among other sources.The growth or decrease that the Port of Tumaco has had in the last years, taking into account that in order to participate in International Trade the ports They are fundamental.